Stable carbon isotope fractionation data between H2CO3* and CO2(g) extended to 120 °C. (18th June 2014) - Myrttinen, A.; Becker, V.; Mayer, B.; Barth, J. A. C.
<x xml:space="preserve">Abstract</x> RATIONALE Literature data on experimentally derived equilibrium stable carbon isotope fractionation (103lnα13C) between H2CO3* (H2CO3 + CO2(aq)) and gaseous CO2 (CO2(g)) are so far only available up to 60 °C and were typically determined at or near atmospheric pressures. Here we experimentally expand this dataset to temperature and pressure conditions close to the supercritical state for CO2. The objective is to improve the applicability of stable carbon isotopes as a tracer in environments where such conditions prevail. METHODS Eighteen stable carbon isotope laboratory experiments were conducted in a steel vessel. Deionised water that was acidified with hydrochloric acid (HCl, 1 N) to a pH of 2.4 was equilibrated with CO2(g) at pressures (pCO2) of 55 bar for durations between 2 and 188 h. The experiments were conducted at 20, 60, 80, 100 and 120 °C. H2CO3* and CO2(g) were sampled separately and their carbon isotope ratios were determined by isotope ratio mass spectrometry. RESULTS At 20 °C, average 103lnα13CH2CO3*–CO2(g) values of ‐1.0 ± 0.1 ‰ were observed with a preference for 12C in H2CO3* consistent with previous research. At elevated temperatures of 120 °C, 103lnα13CH2CO3*–CO2(g) values decreased to an average value of −0.7 ± 0.1 ‰. The resulting temperature dependence for carbon isotope fractionation between H2CO3* and CO2(g) was 103lnα13CH2CO3*–CO2(g) = (0.0025 ± 0.0004) T(°C) – (1.0 ± 0.03) ‰. Carbon isotope equilibrium between H2CO3* and CO2(g) was reached within reaction times of 18 h and mostly within 5 h or less. CONCLUSIONS 103lnα13CH2CO3*–CO2(g) data are now available for temperatures up to 120 °C and for pressures of up to 55 bar. The results suggest that higher pCO2 levels possibly shorten carbon isotope equilibration times. These data are critically important for using δ13C values as tracers, for instance at geological CO2 sequestration sites and corresponding natural analogues. Copyright © 2014 John Wiley & Sons, Ltd.